8(c-4)=-2(c+6)

Simple and best practice solution for 8(c-4)=-2(c+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(c-4)=-2(c+6) equation:


Simplifying
8(c + -4) = -2(c + 6)

Reorder the terms:
8(-4 + c) = -2(c + 6)
(-4 * 8 + c * 8) = -2(c + 6)
(-32 + 8c) = -2(c + 6)

Reorder the terms:
-32 + 8c = -2(6 + c)
-32 + 8c = (6 * -2 + c * -2)
-32 + 8c = (-12 + -2c)

Solving
-32 + 8c = -12 + -2c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '2c' to each side of the equation.
-32 + 8c + 2c = -12 + -2c + 2c

Combine like terms: 8c + 2c = 10c
-32 + 10c = -12 + -2c + 2c

Combine like terms: -2c + 2c = 0
-32 + 10c = -12 + 0
-32 + 10c = -12

Add '32' to each side of the equation.
-32 + 32 + 10c = -12 + 32

Combine like terms: -32 + 32 = 0
0 + 10c = -12 + 32
10c = -12 + 32

Combine like terms: -12 + 32 = 20
10c = 20

Divide each side by '10'.
c = 2

Simplifying
c = 2

See similar equations:

| -a^2-10a+25=25 | | 4.5(x-4)=-0.5x+22 | | 6(3a+14)=90 | | 0=x^2-32x-5 | | B^2+5b+1= | | 1/2t+3=5 | | (5x/4)+(x+4) | | 10=0.5*2*(6+x) | | 6x+3=9(x-4) | | 8x^2y+12xy^2= | | 6x+3=9x | | 1m-5=3m | | 7/9=y+5 | | 5(c-1)+69=-3c | | 12(x+7)=4(x-1) | | 80+-2y=70 | | 4b^2-9b-34=0 | | U+4/5=-1/6 | | 0=6n-n^2 | | 30x-4=4(2x-0.3) | | -11x^2+1430x-4400=0 | | Y-7/8=-1/2 | | (x-10)+2y=70 | | 6(x-4)=-2x+24 | | 24(1/8y+37.5)+19y=1340 | | 6x+14=-7+x | | 4(x-1)=-3x+31 | | 9(3n-3)=(8n+4)+7 | | 14+6x=7-x | | 6g+7=-29 | | (2x+7)/8-2=x+(x-1)/2 | | 0=7(6-3x) |

Equations solver categories